The Legal Urgency of Government Regulation and Supervision on Qibla Direction and Prayer Time Applications in Indonesia - Muhammad Ikbal; Ahmad Izzuddin; Muhammad Firli Yanto; Novi Arisafitri (International Journal Ihya' 'Ulum al-Din, 2025)
Prayer time and Qibla direction applications have become an integral part of daily religious practices for Muslims. However, with the increasing number of available applications on digital platforms, the accuracy of the information provided by these apps often varies, which can affect the validity of religious practices. This study aims to explore the urgency of government oversight over prayer time and Qibla direction applications to ensure their accuracy and reliability. The research methodology includes a literature review and qualitative analysis of various applications available on the Android platform. The findings indicate that many applications fail to meet the required accuracy standards, particularly concerning prayer times and Qibla direction, potentially misleading users in performing their religious duties. Therefore, this study highlights the importance of government oversight and regulation to ensure these applications adhere to proper guidelines and can be trusted. The author also recommends implementing policies to regulate the feasibility testing of these apps, including standardizing prayer time calculations and utilizing accurate geospatial data for Qibla direction. With stricter oversight, it is hoped that the applications used by Muslims will become more accurate and beneficial in supporting valid worship practices.